Prestasi Belajar IPS Terpadu Ditinjau Dari Motivasi Belajar Dan Keaktifan Berorganisasi Siswa Kelas VII Dan VIII Mts N 1 Surakarta Tahun Ajaran 2016/2017 - RISTANTI, ARUM; , Dra. Titik Asmawati,SE,M.Si (2017)
The purpose of this study was to determine: 1) How high is the motivation of students of class VII and VIII MTS N 1 Surakarta Academic Year 2016/2017. 2) The organizing activeness class VII and VIII MTS N 1 Surakarta Academic Year 2016/2017. 3) There is influence learning motivation and activeness organize class VII and VIII MTS N 1 Surakarta Academic Year 2016 / IPS Integrated 2017terhadap learning achievement. This research is quantitative descriptive research by drawing conclusions through statistical analysis. The population in this study were students of class VII and VII in MTS N 1 Surakarta Academic Year 2016/2017. Samples taken as many as are 40 students. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, F test, t-test, R2, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 3.257 + 0, 694 X1 + 0, 837 X2. The equation shows that the achievement of integrated social studies influenced by the motivation to learn and to organize students' activeness. The conclusions drawn are: 1) Based on hypothesis testing in unison or test F known that the value obtained Fhitung> Ftable is 46.183> 3.320 and the significance value <0.05 is 0.000 <0.05. This means learning motivation and activeness of students to organize jointly contribute positively and significantly to the achievement of an integrated social studies. While the coefficient of determination obtained for 0.508, which means that the contributions made by the combination of variable and activeness of learning motivation to organize the students of 50.8%, while 49.2% is influenced by other variables. 2) Variable learning motivation contribute positively and significantly to the achievement of an integrated social studies. The test results of multiple regression analysis known regression coefficients of the variables of learning motivation in 2013 (b2) of 0, 694 and is positive. Based on t test was obtained for thitung> ttable namely 4.707> 2.042 and the significance value <0.05 is 0.000 <0.05. Learning motivation variable relative contribution of 29% and the effective contribution of 14.7%. 3) Variable liveliness to organize students to contribute positively and significantly to the achievement of an integrated social studies. The test results of multiple regression analysis regression coefficients of the variables known to organize students' activeness (b3) of 0, 837 and is positive. Based on t test was obtained for thitung> ttable namely 7.781> 2.042 and the significance value <0.05 is 0.000 <0.05. Variable liveliness organize students to give the relative contribution of 71% and the effective contribution of 36.1%.